Pengaruh Penerimaan Pajak Daerah dan Investasi Terhadap Produk Domestik Regional Bruto di Provinsi Kalimantan Tengah - Halwatul Adzkia Nafi'ah; Muhamad Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
Regional economic growth is closely related to fiscal capacity and investment performance. This study aims to examine the effect of Local Tax Revenue, Domestic Investment, and Foreign Investment on Gross Regional Domestic Product (GRDP) in Central Kalimantan. This research employs a quantitative approach using time-series data from 1993 to 2023 obtained from the central bureau of statistics. The analytical method applied is multiple linear regression with a logarithmic transformation. The result indicates that local tax revenue, domestic investment, and foreign investment significantly affect GRDP. Partially, local tax revenue and foreign investment are crucial in promoting regional economic growth. Therefore, local government is expected to strengthen fiscal policies and create a conducive investment climate to support sustainable economic development.